Feasibility and Burden of Lay Caregivers Providing Daily Massages to Patients With Cancer Receiving Hospice and Palliative Care. (December 2022) - Moosvi, Karen; Schoppee, Tasha M.; Xavier, Stacy; Henderson, Kristen; Suarez, Marie L.; Yao, Yingwei; Wilkie, Diana J.
Professional massages reduce symptoms experienced by cancer patients, but are costly. A cost-effective way to include this therapy routinely in hospice care is to teach family caregivers to give massages as part of their caregiving activities. However, the burden on caregivers is unknown and might offset patient benefits or cost savings. The pilot study aim was to explore feasibility issues related to licensed massage therapists training caregivers to give massages at home, the burden of giving four daily massages to hospice patients, and feedback about the training and massage delivery. In this pretest/posttest study, caregivers completed the Caregiver Reaction Assessment (CRA), received training on standardized massage techniques from a licensed massage therapist who evaluated their proficiency the following day. Caregivers gave daily massages for 3 days and afterward completed the CRA. Then a researcher interviewed the dyad for feedback about the training and massage delivery. We used paired t tests to evaluate CRA scores and content analysis of interview data. Thirty-nine caregivers (mean age = 46 years, 69% female) completed the study. After training, all but three caregivers provided daily massages. Some caregivers reported minor logistical challenges in massage delivery and documentation, mutual satisfaction, relaxation, and tender moments ranging from laughter and story sharing to closure activities. Mean CRA scores were not significantly different pretest to posttest. We conclude that repeated-dose massages by caregivers to patients dying of cancer is feasible and is worthy of further study to determine the benefits of massage therapy, caregiver and patient experiences, and caregiver burden.